2022
DOI: 10.3390/jcm11216466
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Severe Traumatic Brain Injury and Associated Factors: A Prospective Cohort Study

Abstract: Objective: The presence of focal lesion (FL) after a severe traumatic brain injury is an important factor in determining morbidity and mortality. Despite this relevance, few studies show the pattern of recovery of patients with severe traumatic brain injury (TBI) with FL within one year. The objective of this study was to identify the pattern of recovery, independence to perform activities of daily living (ADL), and factors associated with mortality and unfavorable outcome at six and twelve months after severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…A previous study conducted with 110 patients with consciousness disorders after moderate and severe TBI showed independence in carrying out self-care activities during the first five years after the injury [28]. A study conducted with 131 adults after severe TBI with focal lesions showed an improvement in independence to perform ADL and IADL over time, where approximately 79% of patients had independence in performing ADL at twelve months, while more than half, 54%, were independent in performing more complex activities such as managing finances, using the telephone, shopping, food preparation, and housekeeping [29]. In our study, at twelve months after DAI, 46.3% of patients had the maximum score on the Lawton Scale, indicating complete independence in performing IADL.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted with 110 patients with consciousness disorders after moderate and severe TBI showed independence in carrying out self-care activities during the first five years after the injury [28]. A study conducted with 131 adults after severe TBI with focal lesions showed an improvement in independence to perform ADL and IADL over time, where approximately 79% of patients had independence in performing ADL at twelve months, while more than half, 54%, were independent in performing more complex activities such as managing finances, using the telephone, shopping, food preparation, and housekeeping [29]. In our study, at twelve months after DAI, 46.3% of patients had the maximum score on the Lawton Scale, indicating complete independence in performing IADL.…”
Section: Discussionmentioning
confidence: 99%
“…We propose some possible explanations for these results. First, the follow-up times and methods for measuring tracking progress after TBI differed in the studies [ 48 ]. A recent study revealed that most patients improve within a few days to a few weeks; however, many patients continue to report PCS for months or years, even after very minor head injuries [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study by Oliveira et al ( 2022) involving individuals with severe TBI and focal lesions, it was found that significant functional recovery occurred in the first twelve months after the injury, with the most pronounced improvements observed within the initial three months. This underscores the potential for substantial long-term recovery in severe TBI patients [19]. Through a thorough examination of the current corpus of literature pertaining to long-term outcomes subsequent to severe "Traumatic brain injury (TBI)", the review uncovered a wide range of findings.…”
Section: Discussionmentioning
confidence: 99%